Analisis Pengaruh PDRB, Angkatan Kerja dan Jumlah Penduduk Terhadap Kemiskinan Provinsi Sumatera Utara Tahun 2001-2020 - Bernando Aldo Yosua Tambunan; Elisabeth Silaban; Intan Harahap; Indra Maipita; Muammar Rinaldi (CV. Rayyan Dwi Bharata, 2024)
Poverty is a condition that has not and has never been resolved on this earth. People who are still in poverty are still found in many countries, even in developed countries the phenomenon of poverty is a serious problem. The purpose of this study was to analyze the effect of Gross Regional Domestic Product (GRDPHB), Labor, Population on Poverty in North Sumatra Province. The analysis used in this study is a time series data analysis model, with secondary data for 2001-2020 obtained from the Central Bureau of Statistics (BPS) of North Sumatra.The results obtained from this study are; In the short term, the variables of GRDPHB (LNX1), Labor Force (LNX2), and Total Population do not have a significant effect on Poverty in North Sumatra Province. However, the Error Correction Term (ECT) is significant in the short run, which indicates an adjustment towards the long-run equilibrium after a shock; In the long run, the GRDP variable (LNXI) has a negative and significant effect on Poverty in North Sumatra Province. Meanwhile, the variables of Labor Force (LNYX) and Total Population are not significant. The Error Correction Model (ECM) used in this study can explain about 87% of the variation in the Poverty variable in North Sumatra Province.